Effective Use of Mimosa pudica Leaf Extract on Cyprinus carpio Infected with Aeromonas hydrophila - Lestari, Putri Amelia; ismarica, ismarica; dewiyanti, Irma; Mellisa, Siska; Afriani, Sari; Dewi, Cut Dara (JURNAL AKUAKULTURA, 2024)
This study aims to determine the effect of giving Mimosa pudica leaf-soaking extract to Cyprinus carpio fish infected with Aeromonas hydrophila. This research was conducted in the Laboratory of Fish Hatchery and Breeding, Faculty of Marine and Fisheries, Syiah Kuala University and the method used a complete randomized design (CRD) with 4 treatments (A: Mimosa pudica extract 0%, B: Mimosa pudica extract 3%, C: Mimosa pudica extract 5%, D: Mimosa pudica extract 7%). The results of this study indicate that Mimosa pudica extract affects the clinical symptoms of Cyprinus carpio. Data from ANOVA analysis showed that the administration of Mimosa pudica extract had a significant effect (P<0.05) on survival with each treatment of 36.67±11.54% in treatment A, in treatment B of 56.67±5.77%, in treatment C of 66.67±5.77% and in treatment D of 83.33±5.77%. Leukocyte results in all treatments showed differences in values where each was in treatment A at 29.5 104 cells/mm3 , in treatment B at 19.5 104 cells/mm3, in treatment C at 15.4 104 cells/mm3, and in treatment D at 7.21 104 cells/mm3. The haemoglobin results of all treatments also had different values, namely in treatment A of 3.4 g/dl, treatment B of 4.2 g/dl, treatment C of 5.2 g/dl, and treatment D of 6 g/dl. The conclusion from the results of this study is that 7% Mimosa pudica leaf extract shows the best results on clinical symptoms, survival, leukocyte count and haemoglobin levels.